Tindak Tutur dalam Ungkapan Grafiti pada Bak Truk di Pelabuhan Merak, Cilegon, Banten: Speech Acts on Graffiti Expressions on The Back of a Truck at Merak Port, Cilegon, Banten - Aziz Fauzi; Dwi Nur Hidayatullah (Balai Bahasa Provinsi Papua, 2021)
This study aims to classify and explain the form of speech acts on graffiti expressions on the back of a truck at Merak Port, Cilegon, Banten. The research method used is descriptive qualitative. The data of this research are in the form of fragments of graffiti utterances on the back of a truck at Merak Port, Cilegon. The data were collected using literature study techniques, note-taking techniques, and documentation techniques. Data analysis using the Miles and Huberman model, carried out in stages: data collection, data reduction, and data presentation. Through the pragmatic approach, the results show that the graffiti expression on the back of a truck at Merak Port, Cilegon, Banten is in the form of declarative, representative, expressive, directive and commissive speech acts. In addition, it was also revealed the meaning of the cut-off form of speech expression graffiti on the back of a truck at Merak Port, Cilegon, Banten.